ANALISIS PELAKSANAAN TUJUH LANGKAH MENUJU KESELAMATAN PASIEN DI PUSKESMAS LEBDOSARI SEMARANG - Ririn Nurmandhani; Riky Setiawan; Zhulian Alvandi Aphare (Dian Nuswantoro Semarang, 2022)
Patient safety is one of the quality assurance efforts in providing health services. Puskesmas as an institution that provides basic health services must prioritize patient safety. Patient safety incidents still occurred at Puskesmas Lebdosari in the 2019 period, which were 5 incidents and 9 incidents in 2020. The purpose of this study is to analyze the implementation of seven steps towards patient safety at Puskesmas Lebdosari Semarang. This research was a qualitative research with a descriptive approach. Data processing was carried out by interviewing and observing 12 informants, namely 3 main informants and 9 triangulation informants. Based on the results of interviews, seven steps program towards patient safety at Puskesmas Lebdosari has been well implemented. In 2020 there have been no cases of Patient Safety Incidents (IKP). Based on this research, it is suggested that there is a need for a budget plan for patient safety training at Puskesmas Lebdosari in order to support patient safety and carry out improvements in patient safety incident reporting.